Proceedings of the 2021 ACM-SIAM Symposium on Discrete Algorithms (SODA) 2021
DOI: 10.1137/1.9781611976465.95
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Mixing from Spectral Independence beyond the Boolean Domain

Abstract: We extend the notion of spectral independence (introduced by Anari, Liu, and Oveis Gharan [2]) from the Boolean domain to general discrete domains. This property characterises distributions with limited correlations, and implies that the corresponding Glauber dynamics is rapidly mixing.As a concrete application, we show that Glauber dynamics for sampling proper q-colourings mixes in polynomial-time for the family of triangle-free graphs with maximum degree ∆ provided q ≥ (α * + δ)∆ where α * ≈ 1.763 is the uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…v } be the collection of feasible vertex-spin pairs under τ , where Ω τ v represents the set of feasible spins at v conditioned on τ . The following definition is taken from [CG ŠV21]; see also [ALO20,FGYZ21].…”
Section: Spectral Independence Via Stability Of the Partition Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…v } be the collection of feasible vertex-spin pairs under τ , where Ω τ v represents the set of feasible spins at v conditioned on τ . The following definition is taken from [CG ŠV21]; see also [ALO20,FGYZ21].…”
Section: Spectral Independence Via Stability Of the Partition Functionmentioning
confidence: 99%
“…Spectral independence serves as an important technical bridge: for many results established with different approaches, their proofs also imply spectral independence and as a consequence we obtain much stronger running time guarantees. In particular, in [CLV20] it was shown that potential function techniques used for analyzing correlation decay algorithms also imply spectral independence; see also [CG ŠV21,FGYZ21]. Very recent works [BCC + 21, Liu21] prove that path coupling arguments for a broad class of chains, including any local chain, yields spectral independence.…”
Section: Introductionmentioning
confidence: 99%
“…Then for some absolute constant ǫ ≈ 10 −5 , if q ≥ ( 11 6 − ǫ)∆ , then the uniform distribution over proper list-colorings for (G, L) is ℓ ∞ -independent with parameter O(1). Theorem 3.6 (See proof of Theorem 9 [Che+21], see also Lemma 6.1 [Fen+21]). Let ǫ > 0, and suppose that (G, L) is a list colouring instance where G = (V, E) is a triangle-free graph of maximum degree ∆ and L = (L(v)) v∈V is a collection of color lists of maximum length q ≥ (1 + ǫ)α * ∆ + 1, α * ≈ 1.763.…”
Section: Gibbs Distributions Of Spin Systemsmentioning
confidence: 98%
“…A distribution over {−1, +1} is said to be -spectrally independent with all fields if max (Ψ inf ( ) ) ≤ for any = ( ) ∈ ∈ R >0 . The notion of spectral independence was first introduced in [ALO20], then further developed in [CGŠV21,FGYZ21]. Remark that if a distribution is -spectrally independent in ∞-norm with all fields, then it must be -spectrally independent with all fields.…”
Section: F L C U B Fmentioning
confidence: 99%